2016
DOI: 10.1007/s11695-016-2259-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cardiopulmonary Responses to Treadmill Walking Following Gastric Bypass Surgery

Abstract: We have demonstrated that weight loss alone was not sufficient to improve select cardiopulmonary fitness measures during treadmill walking in obese females 3 months after GBS. However, we did observe a significant overall improvement in exercise capacity as the GBS group was able to exercise longer, presumably due to significant reductions in body mass and a subsequent reduced metabolic cost of walking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 36 publications
0
25
0
1
Order By: Relevance
“…Previous studies have also investigated CPET parameters 3–12 months after sleeve gastrectomy or gastric bypass surgery [11, 24, 29-31]. To our knowledge, this is the first study which has correlated the amount of weight loss that is needed to result in improvement of aerobic capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also investigated CPET parameters 3–12 months after sleeve gastrectomy or gastric bypass surgery [11, 24, 29-31]. To our knowledge, this is the first study which has correlated the amount of weight loss that is needed to result in improvement of aerobic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Improved aerobic capacity may be due to better efficiency in performing activities rather than real improvements in cardiorespiratory or muscle function. Even though an increase of VO 2 peak per body weight (mL/min/kg) confirmed better physical functioning and mobility [29-31], absolute aerobic capacity in terms of VO 2 peak (mL/min) was unchanged after bariatric surgery. Nevertheless, in the group which had more than 18% weight reduction, VO 2 peak (mL/min) was significantly reduced after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, treadmill exercise testing studies before and after bariatric surgery showed indeed reduced metabolic costs of body weightbearing activities with lower ventilation cost and a higher dyspnea threshold level [8-10, 17, 19, 29]. However, treadmill studies showed unchanged or reduced absolute VO 2 max after surgery [10,12,17,19,20].…”
Section: Aerobic Exercise Capacitymentioning
confidence: 99%
“…Previous studies evaluating the aerobic exercise capacity (VO 2 max) with a cardiopulmonary exercise test (CPET) before and after bariatric surgery showed controversial results with either an increased [9,10], unchanged [11][12][13][14][15] or decreased VO 2 max [16][17][18][19][20]. This discrepancy results emerged from different population characteristics (body mass index (BMI), age, sex, comorbidities, etc.…”
Section: Introductionmentioning
confidence: 99%
“…En el paciente bariátrico, el objetivo de la evaluación es determinar la capacidad cardiorrespiratoria a través de una prueba de estrés cardiopulmonar que nos permita prescribir el ejercicio aeróbico y evaluar la respuesta al entrenamiento, teniendo en consideración sus experiencias previas habitualmente negativas relacionadas con el ejercicio y/o actividad física 8 . En la literatura revisada en la Tabla 2 6,[9][10][11][12][13][14][15][16][17][18] , la metodología más utilizadas es la evaluación directa del consumo máximo (VO 2max ) o pico de oxígeno mediante ergoespirometría, utilizando protocolos escalonados con duración de 5-12 min. Dentro de las evaluaciones indirectas la realización del protocolo de Astrand o Bruce puede entregar una estimación del VO 2max 19 y parámetros de carga interna y/o externa para la prescripción del ejercicio.…”
Section: Evaluación De La Capacidad Cardiorrespiratoriaunclassified